Penerapan Strategi Digital Marketing dalam Upaya Meningkatkan Pendapatan pada UMKM Sarbini Kepiting di Desa Pinggirpapas Kabupaten Sumenep - Imam Bushiri, Moh; Asiyah, Siti; Farida, Eka (Jurnal SOLMA, 2024)
Background: One of the interesting MSMEs to discuss is the Sarbini Crab MSME which is engaged in the seafood business located in Pinggirpapas Village, Kalianget District, Sumenep Regency, East Java.  Some MSME players still do not use digital marketing as a means of product marketing. This study aims to determine the implementation of digital marketing strategies in an effort to increase income for crab sarbini MSMEs in Pinggirpapas Village. Method: The method used in this study uses SWOT Analysis. Result: The results of this study show that Sarbini MSMEs still have not implemented Digital Marketing strategies such as promoting through social media or online media so that consumers cannot compete widely outside the region. This MSME only has a google map (location) and still does not have social media such as IG, Tiktok and other media. Conclusion: Entrepreneurs should be able to analyze, so from the need to be corrected in the problem of marketing strategies to increase revenue, it should be better to implement digital marketing strategies such as promoting online and creating social media accounts.